2022
DOI: 10.1108/medar-03-2021-1247
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the EU nonfinancial information directive on environmental disclosure: evidence from Italian environmentally sensitive industries

Abstract: Purpose To determine whether to entrust the European Union (EU) to create a new nonfinancial reporting framework or endorse the extant reporting framework developed by the Global Reporting Initiative (GRI), this study aims to explore whether the mandatory implementation of the EU Directive positively impacted the GRI-based environmental disclosure. Design/methodology/approach The authors compared the pre- and post-EU Directive environmental disclosure of 16 Italian environmentally sensitive companies. The au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 85 publications
0
4
0
1
Order By: Relevance
“…It shows that neither the threat of respective regulation (Stanny, 2013) nor actual regulation in place translate into a higher quantity and quality of ER. Vormedal and Ruud (2009) Furthermore, the evidence from Portugal, China and Italy shows that the introduction of ER requirements did not lead to any significant increase in corporate transparency (Ji et al, 2020;Lima Ribeiro & Aibar-Guzmán, 2010;Wang & Bernell, 2013), especially in the provision of hard, objective data (Papa et al, 2022). A similar conclusion may be drawn from the study by Ahmad and Mohamad (2014) i.e.…”
Section: Voluntary Vs Mandatory Ermentioning
confidence: 51%
See 1 more Smart Citation
“…It shows that neither the threat of respective regulation (Stanny, 2013) nor actual regulation in place translate into a higher quantity and quality of ER. Vormedal and Ruud (2009) Furthermore, the evidence from Portugal, China and Italy shows that the introduction of ER requirements did not lead to any significant increase in corporate transparency (Ji et al, 2020;Lima Ribeiro & Aibar-Guzmán, 2010;Wang & Bernell, 2013), especially in the provision of hard, objective data (Papa et al, 2022). A similar conclusion may be drawn from the study by Ahmad and Mohamad (2014) i.e.…”
Section: Voluntary Vs Mandatory Ermentioning
confidence: 51%
“…What is interesting is that the compliance rate after the implementation of the Sarbanes–Oxley Act (SOX) in 2002 is significantly lower than prior to the Act. Furthermore, the evidence from Portugal, China and Italy shows that the introduction of ER requirements did not lead to any significant increase in corporate transparency (Ji et al, 2020; Lima Ribeiro & Aibar‐Guzmán, 2010; Wang & Bernell, 2013), especially in the provision of hard, objective data (Papa et al, 2022). A similar conclusion may be drawn from the study by Ahmad and Mohamad (2014), who find that environmental disclosures of Malaysian public construction companies produced under the stock exchange mandatory reporting regime are incomplete and largely limited to a general narrative and non‐verifiable statements.…”
Section: Resultsmentioning
confidence: 99%
“…Pengungkapan lingkungan didefinisikan sebagai respons terhadap tekanan yang diberikan oleh stakeholder sebagai upaya perusahaan dalam mengelola kesan masyarakat terhadap dampak lingkungan hidup atas aktivitas yang dilakukan (Khan & Iqbal, 2022;Papa et al, 2022). Menurut Raimo et al, (2022), pengungkapan lingkungan merupakan sarana dialog perusahaan dengan stakeholder dengan memberikan informasi tentang dampak lingkungan akibat aktivitas perusahaan.…”
Section: Pengungkapan Lingkunganunclassified
“…Environmental management information is disclosed more frequently by American businesses with superior corporate social responsibility (CSR) records, and the quality of disclosure is outstanding (Koh et al, 2022). With the mandatory implementation of the Non‐Financial Information Directive in the EU, companies are increasingly complying with the Global Reporting Initiative standard, and the total amount of environmental management information disclosed has increased significantly (Papa et al, 2022). Through empirical studies of corporate data, researchers have identified many factors that influence the disclosure of environmental management information, such as a favorable correlation between corporation value and disclosure.…”
Section: Introductionmentioning
confidence: 99%